2011
DOI: 10.1039/c1cc12886h
|View full text |Cite
|
Sign up to set email alerts
|

A general strategy for the synthesis of upconversion rare earth fluoride nanocrystals via a novel OA/ionic liquid two-phase system

Abstract: Herein we report a general strategy to synthesize highly uniform and monodisperse rare earth fluoride nanocrystals through a novel OA/ionic liquid two-phase system, while water-soluble hexagonal NaREF(4) nanocrystals are obtained by adding n-octanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…The synthetic principle and protocol of LaF 3 :Yb,Er UCNPs with different components (various combinations of host materials, sensitizers, and activators) and solubilities (water-solubility and nonpolar solvents-solubility) were reported in our previous works 26, 27. and other groups achievements28, 29 Transmission electron microscope (TEM) and X-ray powder diffraction (XRD) were performed to investigate the morphology and structure of UNCPs.…”
Section: Methodsmentioning
confidence: 99%
“…The synthetic principle and protocol of LaF 3 :Yb,Er UCNPs with different components (various combinations of host materials, sensitizers, and activators) and solubilities (water-solubility and nonpolar solvents-solubility) were reported in our previous works 26, 27. and other groups achievements28, 29 Transmission electron microscope (TEM) and X-ray powder diffraction (XRD) were performed to investigate the morphology and structure of UNCPs.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the Bif-ILEs stabilized the nanostructures from aggregating. Daxiang Cui et al reported a general strategy to synthesize highly uniform and monodisperse rare earth fluoride nanocrystals through a novel OA/ionic liquid two-phase system [56][57][58]. They adopt the notion of liquid-liquid two-phase reaction and devise a novel oleic acid (OA)/1-butyl-3-methylimidazolium tetrafluoroborate (BmimBF 4 ) two-phase system, which combines the merits of thermal decomposition (size and morphology control) and IL-based strategy (mild conditions, user-friendly reagents, and direct water solubility).…”
Section: Ionic Liquid Microemulsionmentioning
confidence: 99%
“…Consequently, our group have adopted the notion of liquid-liquid twophase approach (the advantage of thermal decomposition method) and ILs as fluorine source (the advantage of IL-based strategy) and create a novel IL-OA dual phase method ( Fig. 2), by which hydrophilic and hydrophobic Ln-dopedNaYF 4 ,NaGdF 4 ,NaYbF 4 ,LaF 3 could be selectively synthesized in a one-pot step [33][34][35][36][37]. We are confident that other kinds of UCNPs with excellent morphology and UC emissions can be gained by this method as well.…”
Section: Advances Of Preparation Of Ucnpsmentioning
confidence: 99%